Association of six CpG-SNPs in the inflammation-related genes with coronary heart disease. (July 2016) - Chen, Xiaomin; Chen, Xiaoying; Xu, Yan; Yang, William; Wu, Nan; Ye, Huadan; Yang, Jack; Hong, Qingxiao; Xin, Yanfei; Yang, Mary; Deng, Youping; Duan, Shiwei
Abstract Background Chronic inflammation has been widely considered to be the major risk factor of coronary heart disease (CHD). The goal of our study was to explore the possible association with CHD for inflammation-related single nucleotide polymorphisms (SNPs) involved in cytosine-phosphate-guanine (CpG) dinucleotides. A total of 784 CHD patients and 739 non-CHD controls were recruited from Zhejiang Province, China. Using the Sequenom MassARRAY platform, we measured the genotypes of six inflammation-related CpG-SNPs, includingIL1B rs16944, IL1R2 rs2071008, PLA2G7 rs9395208, FAM5C rs12732361, CD40 rs1800686, andCD36 rs2065666). Allele and genotype frequencies were compared between CHD and non-CHD individuals using the CLUMP22 software with 10, 000 Monte Carlo simulations. Results Allelic tests showed thatPLA2G7 rs9395208 andCD40 rs1800686 were significantly associated with CHD. Moreover, IL1B rs16944, PLA2G7 rs9395208, andCD40 rs1800686 were shown to be associated with CHD under the dominant model. Further gender-based subgroup tests showed that one SNP (CD40 rs1800686) and two SNPs (FAM5C rs12732361 andCD36 rs2065666) were associated with CHD in females and males, respectively. And the age-based subgroup tests indicated thatPLA2G7 rs9395208, IL1B rs16944, andCD40 rs1800686 were associated with CHD among individuals younger than 55, younger than 65, and over 65, respectively. Conclusions In conclusion, all the six inflammation-related CpG-SNPs (rs16944, rs2071008, rs12732361, rs2065666, rs9395208, and rs1800686) were associated with CHD in the combined or subgroup tests, suggesting an important role of inflammation in the risk of CHD.